Biosorption of chromium (V1) from electroplating wastewater using acinetobacter calcoaceticus 3 grown in pineaple waste - Nordiana Nordin, 1981- (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2006